Study of Critical Point Analysis on Meat-Based Foods in Bandung - Adawiyah, Ayuni; Kulsum, Yuni (UIN Sunan Gunung Djati Bandung, 2019)
Halal is a term of lawful or permitted to do according to Islamic law which regulates all aspects of life especially in consuming food. Halal critical point is a condition of food processing. Halal food has a possibility transformed into haram if there are non-halal ingredients used during the food processing. The concept of Halalan Tayyiban is not widely understood by the Muslim, although it is necessary for all human according to health and hygiene. This research was a descriptive study with a qualitative approach. The interview and observation to 8 informants were carried out to the seller of sausages (chicken and beef), cilok, burger, bump and three types of meatballs. The results of the halal condition analysis of processed meat-based foods which is supported by the results of observations and interviews directly pursed into two main important discussions, namely in terms of the composition and processing of processed meat-based food.